Reasonable Accommodation for Deaf / Hard of Hearing Children in Uganda’s Education System - Initiative for Social and Economic Rights (ISER) (Initiative for Social and Economic Rights (ISER), 2013)
The Right to Education is guaranteed under Article 30 of the Constitution of the Republic of Uganda, and the country is party to International Conventions that guarantee the right, including the International Convention on Economic, Social and Cultural Rights. The country has been praised for introducing free Universal Primary Education (UPE) and is scoring relatively well on Millennium Development Goal 2 with very high enrollment figures. Uganda also introduced Universal Secondary Education (USE).